Hydrogeochemical characteristics and groundwater quality investigation along the basinal cross-section of Pravara River, Maharashtra, India - Aher, Sainath; Deshmukh, Keshav; Gawali, Praveen; Zolekar, Rajendra; Deshmukh, Pragati (My University, 2022)
The groundwater samples collected along the cross-section of Pravara river basin is quite distinct in terms of geo-hydrologic and anthropogenic situation. Innovative methods were used to investigate hydrogeochemical phases and groundwater quality for which 33 groundwater samples collected and analysed for pH (7.6–8.7), EC (311–1851 μS/cm), TDS (306–1990 mg/l), Na+ (11–296 mg/l), K+ (0.6–2.2 mg/l), Ca2+ (90–2001 mg/l), Mg2+ (1–17.9 mg/l), Cl− (71–1036 mg/l), SO42− (17–118 mg/l), NO3− (5.1–14 mg/l), CO32− (14.4–40.8 mg/l), HCO3− (117–698 mg/l) and F− (0.05–1.34 mg/l). The water quality was inferred with the help of water quality index (WQI) and Wilcox diagram. Fluid properties and irrigation water characteristics, as well as ion balance and Piper diagram were coupled to explore the type of water. Resourcesat-2 satellite image was processed to know the land use land cover (LULC) of area and its effect on groundwater. The results of pH, K+, Ca2+, Mg2+, SO42−, and NO3− were found within the prescribed limit. According to WQI, total 10 samples on RS and 09 samples on LS were found to have excellent quality water (57.58%) and 04 samples on RS and 05 samples on LS are good water (27.27%). The resulting Wilcox diagram also classifies the groundwater as excellent to good and good to permissible. The hydrochemical facies found Ca2+-Cl− type along RS and Mg2+-HCO3− type along LS. Based on hydrogeochemical characteristics and groundwater quality, the cross sectional aquifer is inferred to be predominantly influenced by natural as well as man induced causes, which have been validated by LULC results.
Keywords: River cross-section; WQI; Hydrogeochemical characteristics; Groundwater quality; Water Quality Index Pravara River Maharashtra India; Pravara River; Maharashtra; India